2003
DOI: 10.1677/joe.0.1780301
|View full text |Cite
|
Sign up to set email alerts
|

Activating point mutations in cyclin-dependent kinase 4 are not seen in sporadic pituitary adenomas, insulinomas or Leydig cell tumours

Abstract: Cell cycle dysregulation is one of the defining features of cancer. Cyclin-dependent kinase 4 (CDK4), together with its regulatory subunit cyclin D, governs cell cycle progression through the G1 phase. Cyclin-dependent kinase inhibitors, including p16 INK4A (encoded by CDKN2A), in turn regulate CDK4. In particular, dysregulation of the p16/CDK4/cyclin D complex has been established in a variety of types of human tumours. Dominant activating mutations affecting codon 24 of the CDK4 gene (replacement of Arg24 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…Cyclin-dependent kinase 4 (CDK4) is the chief catalytic subunit of the regulatory cyclin D that governs G1-to-S phase cell cycle progression (50). Dominant activating mutations affecting codon 24 of the CDK4 gene (R24H or R24C) render CDK4 insensitive to p16INK4 inhibition and are responsible for multiple neoplasia developing (50,51). Collectively, these data indicated that CDK4 mutation may play a role in oncogenesis in a subset of NPC patients.…”
Section: Pik3ca Braf Egfr Kit Kras Hras Nras Pdgfra and Metmentioning
confidence: 99%
“…Cyclin-dependent kinase 4 (CDK4) is the chief catalytic subunit of the regulatory cyclin D that governs G1-to-S phase cell cycle progression (50). Dominant activating mutations affecting codon 24 of the CDK4 gene (R24H or R24C) render CDK4 insensitive to p16INK4 inhibition and are responsible for multiple neoplasia developing (50,51). Collectively, these data indicated that CDK4 mutation may play a role in oncogenesis in a subset of NPC patients.…”
Section: Pik3ca Braf Egfr Kit Kras Hras Nras Pdgfra and Metmentioning
confidence: 99%
“…gip2 , and CDK4 genes, as a possible explanation for the phenotypical variability. However, no activating mutation was found in these genes previously reported to be involved in the pathogenesis of Leydig-cell tumours [3,4,5,6,7,8,9,10,11]. …”
Section: Resultsmentioning
confidence: 99%
“…Further, testes sparing enucleation of a Leydig-cell tumour seems to be sufficient in childhood, but the boy’s scrotum and further development needs ongoing follow-up as rarely a malignant process may occur in the future [23]. In addition, considering the previously reported mutations found in a few of Leydig-cell tumours [3,4,5,6,7,8,9,10,11], the absence of any activating mutations in LHR , as well as in both the ‘hot spot’ regions within the G-alpha subunits ( gsp and gip2 ) and in the regulatory ‘hot spot’ of the CDK4 genes in our patients, indicates molecular heterogeneity among Leydig-cell tumours, corresponding to its highly variable phenotype, which has not been reported previously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations